2001
DOI: 10.1176/appi.ajp.158.6.857
|View full text |Cite
|
Sign up to set email alerts
|

Depression in the Planet’s Largest Ethnic Group: The Chinese

Abstract: The existing evidence supports the hypothesis that the Chinese tend to deny depression or express it somatically. However, Western influences on Chinese society and on the detection and identification of depression are likely to have modified the expression of depressive illness quite sharply since the early 1980s. Analyzing these changes may provide useful insight into the evolution of the diagnosis of depression in Western and other cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
174
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(185 citation statements)
references
References 40 publications
7
174
2
Order By: Relevance
“…Comprising nearly a quarter of the world’s population, the Chinese are the single largest ethnic group and constitute the largest Asian subgroup in the United States. 1,2 According to Census estimates, there are over 3.1 million Chinese individuals residing in the United States and almost half a million are located in New York City (NYC). 3 Despite their presence, the health status of Chinese Americans, and particularly recent Chinese immigrants, is poorly understood as they remain underrepresented in health surveys.…”
mentioning
confidence: 99%
“…Comprising nearly a quarter of the world’s population, the Chinese are the single largest ethnic group and constitute the largest Asian subgroup in the United States. 1,2 According to Census estimates, there are over 3.1 million Chinese individuals residing in the United States and almost half a million are located in New York City (NYC). 3 Despite their presence, the health status of Chinese Americans, and particularly recent Chinese immigrants, is poorly understood as they remain underrepresented in health surveys.…”
mentioning
confidence: 99%
“…For example, it has been suggested that Asian sociocultural factors (e.g., traditional cultural concepts with elements of -fatalism‖) may provide some protection against depression (Parker et al, 2001b). This reasoning is consistent with the growing evidence showing that compared to Westerners, Asians are more likely to accept negative emotions as inevitable and as a part of reality (e.g., viewing…”
Section: Nationssupporting
confidence: 59%
“…The most developed of these suggests that in Chinese culture, mental illness is often viewed as a weakness of character and a cause of family shame (Mak & Chen, 2010;Parker, Gladstone, & Chee, 2001b). Consistent with this reasoning, several studies have shown that stigma associated with depression is more severe among Asians than Caucasian Americans (Chan & Parker, 2004;Chung & Wong, 2004;Hsu et al, 2008).…”
Section: Why Do Chinese People Emphasize Somatic Symptoms?mentioning
confidence: 98%
“…Poor communication skills would make such an adaptive process even more difficult. 13 Moreover, access to health care is also likely to be impaired.…”
Section: Discussionmentioning
confidence: 99%